(untitled) (Vietnam Journal of Community Medicine, 2024)
Objective: Evaluate treating ovarian cyst ruptured by laparoscopic. Subject and methods: 26 patients who underwent laparoscopic surgery to treat ruptured ovarian cyst at Thanh Nhan hospital from January 2019 to June 2023. Results: The disease was common in the age group <35 years with 77%. Common clinical symptoms were abdominal pain, some severe cases showed hemorrhagic shock (34,6%), and menstrual disorders were uncommon. The most common injury is ruptured bleeding of the ovarian cyst (65,4%). The most common size was 2-3 cm (73,1%). In this study, 65% of cases had > 500 ml of blood in the abdomen, and Three of them had > 1000 ml. 100% of patients underwent ovary-conserving surgery. 92,3% had early surgery which was performed under 24 hours. 100% no complications in surgery. Conclusion: Ovarian cyst rupture can cause hemorrhagic shock and should be diagnosed and treated early. The main treatment method is laparoscopic surgery to preserve the ovaries.